2022-RA-865-ESGO Oncologic and fertility outcomes in advanced stage immature teratomas. (20th October 2022) - Marino, Giuseppe; Grassi, Tommaso; Negri, Serena; Testa, Filippo; de Ponti, Elena; Giuliani, Daniela; Marchette, Martina Delle; Sina, Federica; Vicini, Debora; Fumagalli, Diletta; Marchetta, Liliana; Bonazzi, Maria Cristina; et al.
Abstract : Introduction/Background: Malignant ovarian germ cell tumors (MOGCTs) are rare tumors that account for approximately 5% of all ovarian cancers. Immature teratomas (ITs) represent about one third of all MOGCT. The ITs' peak of incidence is 15–30 years old, when the childbearing desire is frequently not completed. Even if most MOGCTs are diagnosed at an early stage, however advanced stages can be found. Our primary aim was to investigate the oncologic outcome of this population and the safety of a fertility sparing surgery (FSS). Secondarily, we have investigated fertility outcomes in patients with advanced stages ITs who underwent FSS. Methodology: Clinicopathological data were retrospectively collected and analyzed from a cohort of patients with advanced stages ITs at San Gerardo Hospital (Monza, Italy) between 1980 and 2019. Results: Seventeen patients were included in the study (4 stage II, 12 stage III and 1 stage IV). Of them, 13 underwent FSS and 4 patients received a demolitive surgery. 13 patients received adjuvant chemotherapy (CT) after surgery, and 4 patients were followed with active surveillance. Four patients (31%) who underwent FSS experienced recurrence. All patients are still alive and without evidence of disease during the last follow up. Among nine patients who attempted to become pregnant after FSS, six got pregnant, showing a fertility rate of 67%. Conclusion: Despite the small number of this population, this is one of the largest case series based only on patients with advanced stage ITs. FSS appears to be a feasible treatment for advanced stage ITs. Furthermore, FSS followed by adjuvant chemotherapy allows pregnancy in young women whose maternal desire was not yet ultimate.